(Auto)Biography of Hurt: Representation and Representability of Rape in Feminist Performance Art - Ana Fazekaš ([sic])
Rape is a crime so close and personal, a trauma so individual, yet an experience so grotesquely impersonal, collective and inherent in our culture that it has a distinct place in the artistic practice of many feminist authors fighting for a voice where the cry had been muffled, refusing to be reframed into another masculinist fantasy of violence. Resistance through performance art as a mode of expression, its power and limitations, is what this article attempts to approach and start to untangle. When it comes to the artistic mode that prides itself most on its closeness to life and body – when there is pain, the pain is real – this paper aims to answer the following questions: how does one approach a violent invasion of a person’s body and self in a culture that perpetuates the mass psychology of rape (Brownmiller), and what can it mean to those who stand by and watch? Keywords: rape, feminism, performance art, autobiography, representation, representability, pain